Bioaccumulation and morphological traits in a multi-generation test with two Daphnia species exposed to lead - Araujo, G. S.; Pavlaki, M. D.; Soares, A. M.V.M.; Abessa, D. M.S. [UNESP]; Loureiro, S. (My University, 2019)
Anthropic pressure negatively affects natural environments. Lead (Pb) is a non-essential highly toxic metal that is present in aquatic ecosystems. Two daphnid species from two different latitudes, the temperate Daphnia magna and the tropical Daphnia similis were used as test-organisms to evaluate a long-term Pb exposure. Both species were exposed for nine generations to a chronic concentration of Pb (50 μg/L) and the effects were explored, considering some endpoints not commonly used in toxicity tests: body burden of Pb and presence of granules in the dorsal region of neonates, hemoglobin contents, carapace deformation and morphology, production of males and ephippia (or dormant haploid egg), changes in the eggs' colour and eggs abortion. This multi-generation test was conducted under two food regimes, the usual (3 × 105 cells/mL) and the restricted (1.5 × 105 cells/mL) regime. On generation F6, Pb acclimated neonates were changed to a clean media for three generations, to evaluate exposure retrieval (recovery period). Negative and adverse effects occurred through generations, but no disparity was shown between D. magna and D. similis. The D. magna Pb accumulation showed different patterns regarding food regime. Bioaccumulation was faster under usual food, rapidly reaching a saturation point, whereas a gradual increase occurred under food restriction. A successful retrieval happened regarding Pb in D. magna, since no difference between control and recovering organisms was evidenced regarding their Pb body burdens. Generational Pb exposure led to carapace malformations, Pb aggregation in neonates' dorsal region, reddish extremities, production of males, ephippia (or dormant haploid egg), and aborted eggs, and changes in the eggs’ colour (green and white). Food restriction also induced the production of males. Reddish extremities disappeared in recovering organisms and ephippia (or dormant haploid egg) did not occurred during the recovery period. Existent males revealed a shorter lifespan than females (under stress). D. magna and D. similis presented similar responses, for the endpoints analysed; however, it does not mean that this lack of sensitivity difference will be observed when other endpoints (e.g. survival, reproduction) are considered. Bioaccumulation of Pb and adverse effects occurred at the tested concentration of 50μg/L, although higher Pb levels are allowed in the environment as safe concentrations, as reported by the Brazilian legislation and the literature where effects are evidences above 400 μg/L of Pb. Pb effects on reproduction, respiration, malformation, and other adverse effects suggest that a chronic generational exposure can be harmful to both D. magna and D. similis, and that such chronic contaminated environments should not be disregarded when it comes to environmental monitoring.
Keywords: Daphnia; Ephippia; Males; Malformation; Multi-generation; Pb; Reddish extremities